Cesarean section and risk of allergies in Ecuadorian children: A cross‐sectional study. Issue 4 (30th October 2020) - Gorris, Amélie; Bustamante, Gabriela; Mayer, Katharina A.; Kinaciyan, Tamar; Zlabinger, Gerhard J.
Abstract: Background: Studies have shown an association between cesarean section (CS) and increased prevalence of childhood allergic diseases. While these observations have been consistent in industrialized countries, evidence from developing countries is limited. Objective: To assess the association between the mode of delivery and allergic diseases in children aged 3–12 years in Quito, Ecuador. Methods: In this cross‐sectional study, parents were surveyed using an anonymous, standardized questionnaire from the International Study of Asthma and Allergies in Childhood project to assess the presence of asthma, allergic rhinitis, atopic dermatitis, and food allergies in their children. The children's age, sex, birthplace, delivery mode (CS/vaginal), socioeconomic status, and ethnicity were recorded. Other parameters included gestational age, breastfeeding, smoking status during pregnancy, and parental allergic diseases. Results: After adjusting for confounding factors, children delivered via CS were found to have a higher risk of wheezing (odds ratio [OR] = 4.12, 95% confidence interval [CI]: 1.43–11.89), physician‐diagnosed asthma (OR = 24.06; 95% CI: 1.98–292.3), and pimples, or eczema with the itching for 6 months (OR = 2.65; 95% CI: 1.06–6.61) than children delivered vaginally. No association was found between the delivery mode and rhinitis or food allergies. After stratifying by socioeconomic status, CS was only associated with allergic disorders in children of medium/high socioeconomic backgrounds. Conclusions: As seen in industrialized settings, children born by CS in nonindustrialized countries have an increased risk of developing allergic disorders including asthma and dermatitis, compared to those delivered vaginally. Abstract : Study enrollment flowchart. Parents of 400 children did participate in the present study and answered 189 questionnaires. The response rate was 47.25%.